Blockchain Technology in Real-Time Governance: An Indian Scenario. (September 2022) - Pandey, Surabhi; Sen, Chandra
Blockchain, the latest distributed ledger technology, has brought paradigmatic shift to the mode of transaction and communication recently. None of the arenas/sectors/organisations is untouched of the technology globally. Recently, the appliance of the distributed ledger technology into digital currency astonished the global community. The applications, apprehension, risks and prospective of technology, thus, have been analysed periodically. In this article, the authors try to understand the potential scope, complexity and legal dynamics of blockchain in the Indian scenario, intermittently. The basic sources such as reports and documents of NITI Aayog, Working Paper of Ministry of Information and Technology as well as reports of Finance Ministry are taken to start with. Moreover, guidelines and press-releases of the Reserve Bank of India, various judgements of the Indian Supreme Court and Ministers' statements in the Indian Parliament and various initiatives of states have also been taken as references to critically comprehend the convolution of blockchain in the Indian context.